CISSP certification domain 3 : security architecture and engineering video boot camp - Pedersen, Thor (Packt Publishing, 2019)
"Prepare for the 2018 version of the Certified Information Systems Security Professional (CISSP) Certification Exam, which is what you will be tested on until the next CISSP curriculum update in 2021. To pass you obviously need to have the knowledge for the CISSP certification exam, but it is much more than that. It is very much an English exam, you need to answer the questions from (ISC)²'s point of view, in their perfect world. You need to be able to spot the keywords (PKI, policy, asymmetric, BCP) as well as the indicators (first, best, last, least, most). Understand and answer every question from a Manager or a Risk Advisers point of view, NOT from an executive or as a techie."--Resource description page